2010
DOI: 10.1261/rna.2418211
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an RNase J ortholog in Sulfolobus solfataricus: Implications for 5′-to-3′ directional decay and 5′-end protection of mRNA in Crenarchaeota

Abstract: In both Bacteria and Eukaryotes, degradation is known to start at the 59 and at the 39 extremities of mRNAs. Until the recent discovery of 59-to-39 exoribonucleases in hyperthermophilic Euryarchaeota, the exosome was assumed to be the key enzyme in mRNA degradation in Archaea. By means of zymogram assays and bioinformatics, we have identified a 59-to-39 exoribonuclease activity in the crenarchaeum Sulfolobus solfataricus (Sso), which is affected by the phosphorylation state of the 59-end of the mRNA. The prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 38 publications
3
54
0
2
Order By: Relevance
“…1C) demonstrated that RNase J generated similar amounts of UMP from each substrate after a 4-h incubation, confirming its exonucleolytic activity. Since the archaeal and bacterial enzymes discriminate for monophosphate at the 59 end (e.g., Hasenohrl et al 2011), there are two ways to interpret these results. The first one is that Arabidopsis RNase J, unlike the other RNase J enzymes characterized so far, degrades exonucleolytically 59-end monoand triphosphorylated RNAs at a similar rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1C) demonstrated that RNase J generated similar amounts of UMP from each substrate after a 4-h incubation, confirming its exonucleolytic activity. Since the archaeal and bacterial enzymes discriminate for monophosphate at the 59 end (e.g., Hasenohrl et al 2011), there are two ways to interpret these results. The first one is that Arabidopsis RNase J, unlike the other RNase J enzymes characterized so far, degrades exonucleolytically 59-end monoand triphosphorylated RNAs at a similar rate.…”
Section: Resultsmentioning
confidence: 99%
“…RNase J contains a b-CASP metallo-b-lactamase fold and is essential for viability in B. subtilis, although the molecular basis for this is still unclear. RNase J is not found in E. coli; however, it is present in cyanobacteria and Archaea (Clouet-d'Orval et al 2010;Hasenohrl et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…We have put forward a model specifying that either trimeric SsoIF2 or SsoIF2γ alone binds to the 5′-terminal end of mRNAs and protects them from 5′ to 3′ directional decay during nutrient limitation, for example, when they grow chemolithotrophically [12]. This hypothesis was supported by the discovery of the S. solfataricus RNase aCPSF2 displaying 5′-to-3′ directional mRNA decay, which was shown to be impeded in vitro by SsoIF2γ bound to the 5′-terminal triphosphate end of RNA substrates [24,25]. This would result in 5′-end protection of the respective mRNAs under conditions when translation is decreased.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Because the removal of just a few nucleotides from the 5= end of leaderless transcripts that have very short or no 5= UTRs is sufficient to disrupt the translation initiation site, it is reasonable to assume that the 5= end of leaderless transcripts should be properly protected against degradation by RNases. In this context, the strong preference for AUG as the start codon of leaderless transcripts in haloarchaea not only allows for efficient translation initiation, it also has the advantage of improving the affinity of ribosome binding to protect leaderless transcripts against degradation through preventing access of a 5=-end-dependent RNase, such as RNase E-like endoribonuclease (57) or RNase J-like 5=-to-3= exoribonuclease (58), to the 5= end of the transcript. The AUG 2 -initiated translation of the sptA transcript most likely occurs via the SD-less mechanism, which neither involves ribosome scanning from the 5= end of the transcript nor makes use of the SD mechanism for translation initiation at 5= UTRs (8,9).…”
Section: Discussionmentioning
confidence: 99%